Perceived post-restructuring job insecurity: The impact of employees' trust in one's employer and perceived employability - Alexandra Arnold; Bruno Staffelbach (Zeitschrift für Personalforschung (ZfP), 2012)
The aim of this study is to investigate whether trust in one's employer and also perceived employability are able to reduce employees' perceived post-restructuring job insecurity. Both, quantitative job insecurity (insecurity over the continuity of a job) and qualitative job insecurity (insecurity over the continuity of valued aspects of the job) are examined. Based on Lazarus' theory of stress, we predict that employees' trust in their employer, perceived levels of employability and the combination effect impacts employees' perceived post-restructuring quantitative and qualitative job insecurity. Results taken from a sample of 377 employees working in Switzerland who survived restructuring mostly support these hypotheses. In general, employees with a high level of trust in their employer and high level of perceived employability show lower post-restructuring quantitative and qualitative job insecurity. Moreover, results suggest a potentially important role for the multiplicative effects of trust in one's employer and perceived employability regarding the perception of qualitative job insecurity. Implications for both research and practice are discussed. – – Diese Studie untersucht, ob mithilfe von Vertrauen in den Arbeitgeber und wahrgenommener Arbeitsmarktfähigkeit der arbeitnehmerseitigen Verunsicherung nach Restrukturierungen entgegengewirkt werden kann. Dabei wird sowohl die quantitative Arbeitsplatzunsicherheit (Unsicherheit bezüglich des Fortbestandes des Arbeitsplatzes) als auch die qualitative Arbeitsplatzunsicherheit (Unsicherheit bezüglich des Fortbestandes wichtiger Arbeitsplatzkomponenten) betrachtet. Basierend auf der Stresstheorie von Lazarus wird vorausgesagt, dass das Vertrauen in den Arbeitgeber, die wahrgenommene Arbeitsmarktfähigkeit und deren Zusammenspiel die wahrgenommene quantitative und qualitative Unsicherheit nach einer Restrukturierung beeinflussen. Die Daten von 377 Arbeitnehmenden in der Schweiz bestätigen mehrheitlich die Hypothesen. Generell zeigen Arbeitnehmende mit hohem Vertrauen in ihren Arbeitgeber und hoher wahrgenommener Arbeitsmarktfähigkeit geringere quantitative und qualitative Unsicherheit nach einer Restrukturierung. Zudem deuten die Ergebnisse auf eine potentiell wichtige Rolle für multiplikative Effekte von Vertrauen in den Arbeitgeber und der wahrgenommenen Beschäftigungsfähigkeit für die qualitative Arbeitsplatzunsicherheit hin. Implikationen für die Forschung und Praxis werden diskutiert.
Keywords: C30; D80; G34; J63; O52; 650; trust in one's employer; perceived employability; perceived quantitative and qualitative job insecurity; restructuring; Lazarus' theory of stress; Organisatorischer Wandel; Vertrauen; Arbeitsplatzwechsel; Beschäftigungsfähigkeit; Schweiz